White Spot Lesions Among Patients Treated With Fixed Orthodontic Appliance at Different Time Intervals - Alidan , Elaf Abdul Kareem; Alrawi , Nadia Alrawi A. (Journal of Baghdad College of Dentistry, 2017)
ABSTRACT Background:- White spot lesions are common esthetic problem that compromise the success of orthodontic treatment. This study aimed to assess white spot lesions in patients with fixed orthodontic appliance at different time intervals. Materials & Methods:- Thirty two patients (24 females and 8 males) were included in this study and they underwent clinical examination for white spot lesions using enamel decalcification index at four time intervals: (2-3 weeks after appliance insertion, 2, 4 and 6 months). Results:- The patients were free of white spot lesions at the appliance insertion visit. The mean of white spot lesions was 2.22 which were increased significantly during six months to reach 24.59 at the end of study. There was a significant difference between the maxillary and the mandibular arches, however, there was no significant difference found between the right and the left sides in both arches. The total numbers of teeth affected by white spot lesions were 74.61% after six months of treatment. Maxillary second premolar and mandibular canine were the most affected teeth; whereas the gingival area around the orthodontic brackets was the most affected area. Conclusion:-Orthodontic patients had a high risk for development of white spot lesions.